Optimising nitrogen management through conjoint application of conventional and nano-urea in wheat (Triticum aestivum) - SINGH, PRATIBHA; SINGH, SURENDRA; SAMMAURIA, RAKESH; GUPTA, SHWETA; SINGH, MAHENDRA; YADAV, M R; SINGH, AJEET; SINGH, SHAILENDRA (The Indian Journal of Agricultural Sciences, 2026)
The study was carried out during the winter (rabi) seasons of 2019–20, 2020–21 and 2021–22 at Rajasthan Agricultural Research Institute (Sri Karan Narendra Agriculture University, Jobner), Durgapura, Jaipur, Rajasthan evaluate the effect of nitrogen management through combined application of nano-urea and different levels of conventional urea on growth indices, productivity and economics of wheat (Triticum aestivum L.) (var. Raj 4238). The experiment was laid out in a randomised block design (RBD) with 10 treatments [T1, Control (100% recommended doses of PKSZn + 0% RDN ); T2, T1 + 120 kg N/ha (100% RDN); T3, T1 + one nano-urea spray; T4, T1 + two nano-urea sprays; T5, T1 + 50% RDN (60 kg N/ha) + one nano-urea spray; T6, T1 + 50% RDN (60 kg N/ha) + two nano-urea sprays; T7, T1 + 75% RDN (90 kg N/ha) + one spray of nano-urea; T8, T1 + 75% RDN (90 kg N/ha) + two sprays with nano-urea; T9, T1 + 100% RDN (120 kg N/ha) + one spray with nano-urea; T10, T1 + 100% RDN (120 kg N/ha) + two sprays with nano-urea] replicated three times. Over three years of experiment, it was observed that 100% RDN (120 kg N/ha) and 75% RDN (90 kg N/ha) alongwith one or two sprays of nano-urea @2.5 mL/L water significantly improved growth parameters, yield attributes and grain yield than100% RDN alone. The application of 50% RDN alongwith two sprays of nano-urea performed at par with 100% RDN alone. However, the combination of 75% RDN with two sprays of nano-urea recorded the highest benefit-cost ratio and net returns. Hence, applying 75% RDN along with two foliar sprays of nano-urea may be considered an efficient strategy to enhance wheat productivity while economising urea consumption.